EVALUASI EKONOMI DENGAN METODE TRAVEL COST PADA TAMAN WISATA PULAU PAHAWANG KABUPATEN PESAWARAN - Rofiiqoh Al-Khoiriah; Fembriarti Erry Prasmatiwi; M Irfan Affandi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
This study aims to analyze the travel cost tourist should pay, to find out the factors that influence visiting frequency, and  economics value of the Pahawang Island tour garden in Pesawaran Regency based on travel cost analysis.  The research used survey method in which location was chosen purposively in Pahawang Island tour garden, Marga Punduh Subdistrict of Pesawaran regency.  The respondents are 40 tourists who were visiting Pahawang Island tour garden of Pesawaran Regency.  Data of this research were collected in April-Desember 2016 and analyzed by linear multiple and travel cost analysis.  The result showed that the average of tourist travel cost were Rp459.726.  The factors influenced visiting frequency were distance and travel cost.  The amount of economics value of Pahawang island tour garden were Rp6,944,262,295,082.  Key words: economics value, travel cost, visiting frequency